Woman-Initiated Divorce and Feminist Fiqh in Indonesia: Narrating Male Acts of Nushūz in Marriage - Atun Wardatun; Bianca J. Smith (Ulumuna, 2020)
This article examines the issue of woman-initiated divorce (cerai gugat) for the controversial reason in Indonesian Islam known as nushūz suami or a husband’s disobedience in marriage. In contrast to the Indonesian Compilation of Islamic Law which applies nushūz (disobedience) to wives only, our arguments draw on feminist jurisprudence (fiqh) to show how nushūz also applies to husbands who do not fulfill marital obligations. A husband’s nushūz is overlooked by classical scholars and Indonesian Islamic Law alike, yet when understood in a Qur’anic feminist context, it gives a depth of understanding about women’s choice to divorce as part of a wider gender justice process and the ‘gendering’ of divorce. Based on women’s post-divorce narratives about nushūz, we propose a feminist fiqh understanding of gender equality situated in tawḥīd as a concept with the potential to form egalitarian-inspired persons (muslimah reformis) and ‘essential’ and ‘true’ justice (keadilan hakiki), through reading religious texts and producing knowledge and policies that include women’s experiences and voices along with those of men’s (mubādalah).